Parental reporting of adverse drug reactions in South Africa: An online survey - Shavani Pillay; Mwila Mulubwa; Michelle Viljoen (AOSIS, 2021)
Background: The high incidence of adverse drug reactions (ADRs) in children is of global concern. Enhancing the reporting of ADRs could contribute to making safer medicines available to children. Aim: To assess parents' awareness of reporting ADRs and their knowledge on the reporting procedures in South Africa. Setting: South African parents with online access. Method: A quantitative descriptive study was conducted based on an anonymous voluntarily web-based self-administered questionnaire that was distributed through Facebook® and LinkedIn™ to parents in South Africa. Results: The questionnaire was completed voluntarily by 206 respondents. The majority of participants (70.9%) were aware of the term ADR. Significant associations between not being aware of the term ADR and single marital status, lower education level, not having private medical aid and accessing public clinics for medical services were found. The majority (66.5%) of participants did report an ADR to a healthcare professional whilst only 15% reported it to a product manufacturer. More than half of the participants (58.7%) knew how to report ADRs whilst 72.8% knew what type of ADRs to report. Almost a third (32.5%) did not know where more information on ADR reporting could be found or how ADRs could be reported (31.5%). Conclusion: The majority of the respondents were aware of the term ADR, indicative of a good knowledge basis on which ADRs to report and the importance of reporting ADRs. However, gaps in the respondents' knowledge were identified which highlighted specific groups of individuals to be targeted to increase ADR awareness and improve the knowledge on the reporting process.